Kinematic parameters and metabolic power in elite soccer players: A small sided a large sided games comparison - Zlojutro, Nemanja; Eler, Serdar; Joksimovic, Marko; Eler, Nebahat; Marković, Saša; Kukrić, Aleksandar; Goranovic, Kosta (Frontiers in Physiology, 2023)
The aim of this study was to analyze the kinematic parameters of tree different format of small sided games (3v3; 5v5; 10v10) during 1 minute, among elite soccer players in Bosnia and Herzegovina. Data total distance (TD), maximum speed (MS), number of accelerations (nAcc), number of decelerations (nDec), number of sprints (nS), High intensity distance (Z4≥19.8 km/h), sprint distance (Z5≥25.2 km/h) and movements requiring a certain metabolic power (Pmet), were collected using a 20 Hz GPS system Pro2 (GPEXE, Exeliosrl, udinese, Italy), on a total of 307 of individual observations. The results showed that the avarage TD was significantly higher in the 5v5 (135.16±18.78) and 10v10 (133.43±20.06) games (F=64.26, p=0.00) compared to the 3v3 (108.24±11.26). Furthermore, the values of the variables Z4 (8.32±3.38, F=97.59), Z5 (1.84±1.53, F=123.64), nS (0.13±0.10, F=96.14) as well as MS (27.06±1.90, F=139.33), statistically significantly higher (p=0.00) in the 10v10 game compared to the other two game formats. The avarge number of nAcc (0.40±0.32, F=9.86, p=0.00) and nDec (0.62±0.36, F=6.42, p=0.00) is statistically significantly higher in the 5v5 game. The results showed that the 5v5 game is significantly more metabolically demanding Pmet (2.76±0.67, F=66.08, p=0.00) compared to the other two game formats. The data presented in this study can serve for future analysis and comprasion and represent a scientific basic for constructing and programming specific training exercises in soccer.